2020
DOI: 10.1097/bot.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Using Alternative Implants for the Treatment of Hip Fractures (FAITH-2): The Clinical Outcomes of a Multicenter 2 × 2 Factorial Randomized Controlled Pilot Trial in Young Femoral Neck Fracture Patients

Abstract: Objective: To assess whether fixation method and vitamin D supplementation impact the risk of patient important outcomes within 12 months of injury in non-geriatric femoral neck fracture patients. Design: Pilot factorial randomized controlled trial. Setting: 15 North American clinical sites. Participants: 91 adults aged 18-60 years with a femoral neck fracture requiring surgical fixation. Intervention: Participants were randomized to a surgical intervention (sliding hip screw or cancellous screws) and a vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Overall, our results appear largely consistent with a mounting body of vitamin D research questioning previously hypothesized benefits of vitamin D supplementation for nonskeletal pathology. ( 26, 31–35 ) However, our post hoc analyses suggest high doses of vitamin D 3 might confer a modest benefit in clinical fracture healing, but this result requires confirmation in a larger RCT.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Overall, our results appear largely consistent with a mounting body of vitamin D research questioning previously hypothesized benefits of vitamin D supplementation for nonskeletal pathology. ( 26, 31–35 ) However, our post hoc analyses suggest high doses of vitamin D 3 might confer a modest benefit in clinical fracture healing, but this result requires confirmation in a larger RCT.…”
Section: Discussionmentioning
confidence: 87%
“…Among patients with ipsilateral femoral shaft fractures, the FAITH‐2 results detected no differences in the average time to radiographic femoral shaft healing between the groups ( p = 0.52). ( 26 ) Furthermore, vitamin D supplementation did not reduce the risk of other patient‐important complications associated with fracture healing. ( 26 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After enrolling 91 participants in the pilot trial, it was determined a definitive trial would not be feasible [6] . A subsequent analysis of the primary clinical outcome, a composite of fracture-related complications, failed to identify any differences in complications between the surgical and vitamin D treatment groups within the limited sample size [7] . Despite being underpowered for the primary clinical outcome comparison at 12-months, we sought to determine if differences in hip function and HRQL would exist between the treatment groups.…”
Section: Introductionmentioning
confidence: 98%
“…Details of the primary and secondary clinical outcomes of the FAITH-2 pilot trial will be reported separately. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%